Cardiac rehabilitation program: An exploration of patient experiences and perspectives on program dropout. Issue 1 (17th January 2022) - Lee, Monica; Wood, Timothy; Chan, Sammy; Marziali, Elsa; Tang, Tricia; Banner, Davina; Lear, Scott A.
Abstract: Background: Cardiac rehabilitation programs (CRP) are effective evidence‐based secondary prevention programs that reduce morbidity and mortality in patients with cardiovascular disease (CVD). However, participation remains suboptimal, resulting in under‐treatment and greater risk for recurrent cardiac events. Understanding the reasons behind CRP dropout is urgently needed to inform the development of programs that best meet patient needs and support sustained engagement. Aims: The aim of this study was to identify and understand factors impacting CRP dropout from the patient perspective. Methods: A qualitative study using semi‐structured interviews was undertaken to examine the experience of 23 patients who dropped out of a CRP within a large urban hospital in British Columbia, Canada. Data were coded, analyzed using the constant comparison technique, and organized thematically. Results: Participants described multiple challenges when attempting to complete CRP. Analysis of the data led to the identification of three main categories: (1) challenges living with CVD, (2) perceived advantages and disadvantages of CRP, and (3) unmet needs during CRP. Linking evidence to action: In the practice setting, assessment of readiness to engage in CRP, alongside patient preferences and engagement needs, should be undertaken for maximum CRP uptake and completion. Providing diverse modes of CRP delivery, along with exploring the impact of virtual options as compared to traditional in‐person programs, will further advance the CRP evidence and may help address pervasive access barriers.